Humanity's Relationship with Nature, Disturbances and Tourism - Guzmán, L. Ana (2022)
Humanity's relationship with nature evolved with disturbances and balance as key elements. This article analyzes disturbance as an aspect that creates distance between society and nature and the role of tourism; this is done through documentary analysis of facts in history and knowledge of the subject. In consequence, it was obtained that the forms of awareness and bonding were part of the destruction of nature, leading to the extinction of species, fragmentation of ecosystems and deterioration of environmental quality. In relation to tourism, a duality exists in which ecosystems can be degraded or areas of conservation can be established. This leads to the proposition that in the current context, forms of relationship must be reconsidered and the knowledge and needs of the territory revalued.